Race, Neighborhoods, and Sentencing: How Social Conditions and Neighborhood Types Affect Incarceration Disparities. (2nd October 2021) - Donnelly, Ellen A.
Abstract: Crime rates and criminal justice responses to them are unevenly distributed across communities in the United States. When court officials review a new case, they consider whether the alleged offender and incident fit the "normal" profile of a case from a community. Neighborhoods and their conditions, such as economic disadvantage, crime rate, and racial/ethnic composition, may have understudied impacts on disparities in incarceration sentencing. This study evaluates whether the conditions in areas where defendants live and where they offend affect racial differences in incarceration sentences. Doing so allows us to estimate whether sentencing disparities are differentially affected by neighborhood type. Relying on the Gelbach decomposition method to estimate the size and sources of Black–White disparities in incarceration sentencing decisions, the study reveals that economic disadvantage in a defendant's neighborhood of residence increases the likelihood of incarceration and lengthens sentences for Blacks. Conversely, economic affluence in neighborhoods of criminal incident reduces racial differences in sentencing by producing harsher sanctions for Whites. Findings highlight the importance of incorporating neighborhood contexts into assessments of sentencing disparities.